The Effect of Pelvic Rocking and Effleurage Massage on Labor Pain - Andarwulan, Setiana; Latifah, Anik; Qurrota’ayun, Sofa; Rihardini, Tetty (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Women usually experience labor pain at certain times, and it often occurs near full dilation. Labor pain is the cause of discomfort in the labor process. Mothers try to overcome pain by checking themselves with the nearest health worker. Pain treatment can be done pharmacologically and non-pharmacologically. Non-pharmacological treatment can be done by doing body movements and effluent massage. Body movements in the form of pelvic rocking and effluent massage. This type of research is a survey study with a one-group pre-test and post-test design. The population used was 38 respondents, with a sample of 34 using simple purposive sampling. The measuring instrument used to measure was in the form of SOP and observation sheets. Furthermore, data collection was carried out. The data that had been collected was tabulated, scored, coded, and data analyzed using data normality tests, homogeneity tests, and data analysis tests using Wilcoxon signed. The statistical test results obtained a p-value equal 0.000, meaning the p-value less than a (0.05). Thus, it can be concluded that pelvic rocking and effluent massage have an effect on reducing labor pain.